Evaluation of educational intervention on knowledge and awareness regarding glaucoma among working adults in Kelantan, Malaysia - Khang, Chong Wen (2023)
INTRODUCTION Glaucoma is a chronic progressive eye disease that can lead to irreversible vision loss if left untreated. Educational interventions can help increase awareness and understanding of the disease among public, leading to earlier detection and better management of the condition. OBJECTIVE The purpose of this study to determine the level of glaucoma awareness and good glaucoma knowledge among the working adults in Kelantan, Malaysia and their associated factors as well as evaluate the impact of educational intervention on the glaucoma knowledge. METHODS A quasi-experimental study was conducted involving 202 participants which were divided into intervention group and control group. A translated and validated questionnaire which comprised questions on sociodemographic information and 14 close-ended questions on glaucoma knowledge were used to assess glaucoma awareness and knowledge. Each questions was assigned one point for correct answer and zero if incorrect or unsure. Scores of seven or more were considered as good knowledge. Educational intervention on glaucoma were given to the intervention group while control group was given presentation on cataract. Post intervention assessments were completed at one month and three months post intervention. Statistical analysis were used to analyse the level of glaucoma awareness and knowledge, factors influencing the level and the differences in the proportion of good glaucoma knowledge between pre-test and post-test for intervention and control groups. RESULTS A total of 202 participants enrolled for the study with 102 in intervention group and 100 in the control group. The glaucoma awareness level was 64.9% and the good glaucoma knowledge level was 49%. Educational attainment was the only factors significantly associated with good glaucoma knowledge. There was significant increase in the proportion of good glaucoma knowledge in the intervention group one month after the educational intervention (p < 0.001) and the effect persisted after three months (p < 0.003). There was also significant difference in the proportion of good post-test glaucoma knowledge between intervention and control group (p = 0.003). CONCLUSION There are significant gaps in awareness and knowledge about glaucoma in the public, educational interventions can be effective in promoting the glaucoma awareness and better understanding of glaucoma. Public health educational campaigns may be a good step in exposing and educating the public in combating glaucoma.